2009
DOI: 10.1177/1524839908321561
|View full text |Cite
|
Sign up to set email alerts
|

Developing Culturally Tailored Health Belief-Based Intervention Materials to Improve Child and Parent Participation in a Cardiovascular Screening Program

Abstract: The Coronary Artery Risk Detection in Appalachian Communities Project was developed to reduce children's future cardiovascular risk by implementing a school-based screening program statewide. Despite the elimination of environmental barriers related to screening cost and accessibility, only half of eligible children participate in the program each year. The authors used the theory of planned behavior to identify health beliefs associated with screening participation. This article describes the process used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…However, both of these foci were supporting interventions concerning health and well-being. The main areas in 30 articles were supportive lifestyle interventions and concerned: a healthy diet and obesity [ 27 , 36 , 39 , 41 , 47 , 54 , 56 , 60 ], physical activity [ 26 , 36 , 38 , 39 , 41 , 45 , 48 , 54 ], substance abuse such as, alcohol, tobacco and drug use [ 29 , 34 , 40 , 43 , 44 , 51 , 61 , 62 , 65 ], sexual and reproductive health [ 29 , 31 , 42 , 43 , 50 , 64 ], violence [ 29 , 37 ], stress [ 33 ], social skills [ 63 ], health beliefs [ 30 ] and mental health promotion [ 35 ]. In addition to lifestyle issues, eleven of the articles considered issues that supported children and young people with their illness or disease.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, both of these foci were supporting interventions concerning health and well-being. The main areas in 30 articles were supportive lifestyle interventions and concerned: a healthy diet and obesity [ 27 , 36 , 39 , 41 , 47 , 54 , 56 , 60 ], physical activity [ 26 , 36 , 38 , 39 , 41 , 45 , 48 , 54 ], substance abuse such as, alcohol, tobacco and drug use [ 29 , 34 , 40 , 43 , 44 , 51 , 61 , 62 , 65 ], sexual and reproductive health [ 29 , 31 , 42 , 43 , 50 , 64 ], violence [ 29 , 37 ], stress [ 33 ], social skills [ 63 ], health beliefs [ 30 ] and mental health promotion [ 35 ]. In addition to lifestyle issues, eleven of the articles considered issues that supported children and young people with their illness or disease.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies included in the scoping review have used interviews as a data collection method to give a voice to the participants. Focus group interviews was the most common data collection method [ 26 , 27 , 29 34 , 37 , 39 , 41 , 44 , 45 , 47 56 , 59 64 ] while other studies have used individual interviews [ 25 , 28 , 30 , 34 , 36 , 42 , 46 , 48 , 49 , 57 , 58 , 64 ] with children and young people. However, seven of the studies reported including both interviews and surveys to involve the children and young people’s views in the development of the intervention [ 27 , 30 , 42 , 44 , 45 , 48 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An extensive body of research has demonstrated that message tailoring (i.e., providing messages that address each individual's specific concerns, beliefs and experiences) is an effective method for increasing compliance with preventive health behaviors, but to our knowledge has never been applied to parental MMR vaccine hesitancy [17][18][19][20] (though some studies suggest a potential role for message framing and/or decision aids in positively influencing parental MMR vaccine decisions, 21,22 and formative studies suggest a benefit to offering different types of educational materials depending on the degree of parental vaccine hesitancy). 23,24 We tested whether an individually-tailored web-based intervention was more effective than a similar-appearing untailored intervention at improving parental MMR vaccination intention among MMR vaccine-hesitant parents.…”
mentioning
confidence: 99%